Increased Staphylococcus aureus Biofilm Formation on Biodegradable Poly(3-Hydroxybutyrate)-Implants Compared with Conventional Orthopedic Implants: An In Vitro Analysis. Issue 4 (April 2020) - Ferlic, Peter W.; Liebensteiner, Michael; Nogler, Michael; Weinberg, Annelie M.; Kühn, Klaus-Dieter; Coraça-Huber, Débora
Abstract : Objective: To compare the biofilm formation on a biodegradable material, poly(3-hydroxybutyrate) (PHB), with that on conventional titanium (Ti) and steel (St) implant material. Methods: Pins made of the different materials were incubated in Müller-Hinton broth inoculated with 2 × 10 5 colony-forming units (CFU)·mL −1 of Staphylococcus aureus for 2 and 7 days and then sonicated for the disruption of the biofilms. CFU were counted to quantify the number of bacteria in the biofilm, and the cell proliferation assay 2, 3-Bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H- tetrazolium-5-carboxanilid salt was used to evaluate their metabolic activity. Scanning electron microscopy visualized the structure of the biofilm. Results: We found a significantly higher metabolic activity and CFU count in the biofilm of PHB pins compared with St and Ti pins (analysis of variance, P < 0.0001). Scanning electron microscopy revealed structured biofilms on PHB pins already after 2 days of incubation, which was not observed on the other tested implants. Conclusion: PHB implants seem to provide an environment that advantages the formation of biofilms of S. aureus, a common pathogen in implant-related infections. The amount of biofilm is higher on PHB implant compared with conventionally used orthopedic titanium and steel implants. To overcome the potential risk of surgical site infections linked to the clinical use of PHB implants, possible modifications of the material, increasing its antibacterial properties, need to be further investigated. Abstract : Supplemental Digital Content is Available in the Text.